Individual-based and interactional resilience mechanisms in social and healthcare service NPOs during the COVID-19 pandemic: Handling a disruptive extreme context in Austria - Kaltenbrunner, Katharina Anna; Stötzer, Sandra; Grüb, Birgit; Martin, Sebastian (Frontiers in Psychology, 2022)
While Austrian social and healthcare service nonprofit organizations (NPOs) are key performers in the Covid-19 pandemic, we also notice their vulnerability in terms of struggling with this disruptive extreme context. The particularity of disruptive extreme contexts is that organizations commonly can neither anticipate them, nor prepare specific countermeasures or specialized resources for fighting against them (Hällgren, Rouleau, & De Rond, 2018). Thus, we regard organizational resilience based on non-specialized resources as an appropriate approach for dealing with (the struggles of) disruptive contexts. Organizational resilience refers to an organization's ability to resist disruptive extreme contexts while maintaining and adapting functionality and ultimately learning from these extreme contexts by mobilizing and accessing the required resources, behaviours and capabilities (c.f. van der Vegt et al., 2015; McCarthy et al., 2017; Witmer & Mellinger, 2016; Hillmann & Guenther, 2021). Based on 33 expert interviews with NPO top and middle managers we aim to explore individual-based and interactional resilience mechanisms of NPOs in the pandemic. The qualitative content analysis yielded to following results: Individual personality traits (e.g., pragmatisms, flexibility) and attitudes (serenity and optimism) constitute individual-based resilience mechanisms. Moreover, a shared (crisis) understanding (e.g., common sense of direction), social connectedness (e.g., team cohesion) and managerial staff orientation (e.g., a caring attitude) as interactional resilience mechanisms helped to maintain and adapt NPO functioning. Overall, this study reinforces the multilevel nature of resilience in terms of the crucial combination of individual and interactional resilience mechanisms for facing adversity. Moreover, it emphasizes the evolving nature of resilience in terms of the required time for e.g., building trust.